Pentingnya Guru Penggerak dalam Menerapkan Kurikulum Merdeka Belajar - Dwi Sunarti; Zalelah Tri Mutiara; Lenia Mardianti; Sucita Ayu Rahmadia (Yayasan Darussalam Bengkulu, 2024)
The purpose of this study was to motivate teachers of SDN 74 in participating in the teacher mobilization pro-gram. This research is considered important because of the importance of mobilizing teachers in implementing an independent learning curriculum, mobilizing teachers can have an important influence and become a facili-ty for learning change that inspires students and encourages students to be more creative, innovative and in-dependent in the learning process and create an interesting and fun learning environment. The results of this study There are four mobilizing teachers at SDN 74 Bengkulu City, of which two have graduated to become mobilizing teachers and the other two are still in the education stage. while the number of class teachers in elementary school 74 in Bengkulu city is 24 class teachers and there are still many teachers who have not fol-lowed the mobilizing teacher. Driving teachers are important in implementing the independent learning curric-ulum because there are so many benefits in the mobilizing teacher program such as gaining useful knowledge, as inspiration, and being able to see the potential of the teacher.